Political economies of climate change. (31st January 2018) - Paterson, Matthew; P‐Laberge, Xavier
Abstract : Political economy approaches across the social sciences provide powerful explanations for important dynamics within the global response to climate change. This article discusses in particular how they provide explanations of the social origins of greenhouse gas emissions, the dominant policy and governance responses to climate change, recurrent political conflicts over these responses, and the patterns of bargaining between states, businesses, and other actors. Underlying these dynamics are a set of contradictions or tensions between the character of capitalism as a social system and the demands of decarbonizing the global economy, specifically: between the imperative for growth that constrains and shapes responses; concerning the power of large transnational businesses and other incumbent interests to block responses; and over the embeddedness of carbon emissions in daily life. The article explores the implications of these contradictions as well as some of the important theoretical debates about the limits of political economy approaches. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Climate Economics > Economics and Climate Change Abstract : Political economies of climate change: a wordle.